Language Style Analysis in “Downton Abbey: New Era” Movie - Prihatin Puji Astuti; Antika, Ria; Adissa Putri (Universitas Cokroaminoto Palopo, 2024)
Language style is a way of people talking and expressing messages, thoughts, or ideas to others. Everyone will use a different style of language when speaking. This happens for various reasons, including: the interlocutor factor, the purpose of the conversation, the context of the conversation, the time and place where the conversation was carried out, and so on. This study aims to analyze the types of language style and the factors of the use of language style spoken by the actors in the film